Dermoscopic Features Summarization and Comparison of Four Types of Cutaneous Vascular Anomalies - Gao, Jing; Fei, Wenmin; Shen, Changbing; Shen, Xue; Sun, Minghui; Xu, Ning; Li, Qing; Huang, Cong; Zhang, Tingfang; Ko, Randy; Cui, Yong; Yang, Chunjun (Frontiers in Medicine, 2021)
Objective: Dermoscopic features of cutaneous vascular anomalies have been reported, but the described features currently known are limited and not well-understood. The aim of this study is to comprehensively summarize and compare the dermoscopic features of the four different types of cutaneous vascular anomalies [infantile hemangiomas (IH), cherry angioma (CA), angiokeratomas (AK), and pyogenic granuloma (PG)] in the Chinese Han population. Materials and Methods: Dermoscopic features of 31 IH, 172 CA, 31 AK, and 45 PG were collected based on the contact non-polarized mode of dermoscopy at 20-fold magnification. Dermoscopic features including background, lacunae, vessel morphology and distribution were collected and summarized. Additionally, we compared these features by age stage, gender, and anatomical locations in CA. Results: The dermoscopic features of IH included the red lacunae, red/red-blue/red-white backgrounds, and vessel morphology such as linear curved vessels, serpiginous vessels, coiled vessels. For CA, the lacunae appeared reddish brown to reddish blue or only red. In terms of vascular morphology, serpentine vessels, coiled vessels, looped vessels, and curved vessels could be seen in the lesions. A few lesions were black or presented with a superficial white veil. There were statistical differences in red background (P = 0.021), unspecific vessel distribution (P = 0.030), black area (P = 0.029), and white surface (P = 0.042) among different age groups. Red-brown lacunae (P = 0.039), red-blue (P = 0.013), red-white background (P = 0.015), black area (P = 0.016), and white surface (P = 0.046) were of statistical difference in terms of the locations of lesions. Lacunae were also observed in AK, which presented with red, dark purple, dark blue, black. Global dermoscopic patterns that were characterized by a homogeneous area were obvious in all PG lesions, among which 30 (66.7%) were red-white and 15 (33.3%) were red. As for local features, “white rail” lines were detected in 19 (42.2%) lesions and white collarette was seen in 34 (75.6%) lesions. Conclusions: Dermoscopy is an applicable diagnostic tool for the diagnosis of cutaneous vascular anomalies. It is necessary to take into account the age stage and lesion location when we diagnose CA using dermoscopy.